2011
DOI: 10.1016/j.biortech.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolonged hypoxia in autotrophic conditions in the hydrogen production by the green microalga Chlamydomonas reinhardtii in photobioreactor

Abstract: In the context of hydrogen production by the green alga Chlamydomonas reinhardtii, the control of light attenuation conditions is used to set-up anoxia under illuminated and autotrophic conditions, without affecting photosynthetic capacities of cells (as with sulphur deprivation or PSII inhibitors like DCMU). This paper presents a full description of the protocol where the incident photons flux density (PFD) is adapted during cultivation in order to obtain a sufficiently low illuminated fraction γ under 0.25 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
0
39
0
1
Order By: Relevance
“…Microalgae have gained considerable attention and have been studied over the last decade by virtue of their high productivity, carbon sequestration potential and oil yield (Córdoba-Matson et al, 2010;Degrenne et al, 2011;Jena et al, 2011;Kliphuis et al, 2010). Microalgae are found to have higher photosynthetic efficiencies than most photoautotrophic organisms and have 10-50 times higher carbon removal efficiencies than other terrestrial plants (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae have gained considerable attention and have been studied over the last decade by virtue of their high productivity, carbon sequestration potential and oil yield (Córdoba-Matson et al, 2010;Degrenne et al, 2011;Jena et al, 2011;Kliphuis et al, 2010). Microalgae are found to have higher photosynthetic efficiencies than most photoautotrophic organisms and have 10-50 times higher carbon removal efficiencies than other terrestrial plants (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the starch reserves do not seem to be linked to H 2 production [2, 3, 14]. Catabolism of proteins [2, 14] or acetate assimilation/dissimilation [3, 4, 10] are potential processes that can provide reductive power for PSII-independent H 2 production. However, conclusive results to characterizing the main electron source used for PSII-independent H 2 production under this condition are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…From studies in Chlamydomonas under autotrophic conditions, it is concluded that H 2 production is lower relative to mixotrophic conditions (Fouchard et al 2005;Tsygankov et al 2006;Kosourov et al 2007;Tolstygina et al 2009;Degrenne et al 2011), which reveal the importance of the presence of acetate in the medium composition.…”
Section: Optimization Of Medium Composition For H 2 Production In Chlmentioning
confidence: 95%
“…This fact likely reflects the high NADH and electron demand of nitrate reductase and nitrite reductase, respectively, which contributes to the re-oxidation of the PEC and competes with HYDA for electrons. Improvement of the sustainability and efficiency of H 2 production under S deficiency using medium with different initial low S concentrations in mixotrophic (Fouchard et al 2009) and autotrophic (Degrenne et al 2011) cultures have been already performed. Similarly, continuous flow and readdition to the media of low S concentrations have been already assayed to optimize H 2 production Laurinavichene et al 2008;Tamburic et al 2013).…”
Section: Optimization Of Medium Composition For H 2 Production In Chlmentioning
confidence: 99%